Increased Serum Levels of sCD14 and sCD163 Indicate a Preponderant Role for Monocytes in COVID-19 Immunopathology - Gómez-Rial, Jose; Currás-Tuala, Maria José; Rivero-Calle, Irene; Gómez-Carballa, Alberto; Cebey-López, Miriam; Rodríguez-Tenreiro, Carmen; Dacosta-Urbieta, Ana; Rivero-Velasco, Carmen; Rodríguez-Núñez, Nuria; Trastoy-Pena, Rocio; Rodríguez-García, Javier; Salas, Antonio; et al. (Frontiers in Immunology, 2020)
Background. Emerging evidence indicates a potential role for monocyte in COVID-19 immunopathology. We investigated two soluble markers of monocyte activation, sCD14 and sCD163, in covid19 patients with the aim of characterizing their potential role in monocyte-macrophage disease immunopathology. To the best of our knowledge, this is the first study of its kind. Methods. Fifty-nine SARS-Cov-2 positive hospitalized patients, classified according to ICU or non-ICU admission requirement, were prospectively recruited and analyzed by ELISA for levels of sCD14 and sCD163, along with other laboratory parameters, and compared to a healthy control group. Results. sCD14 and sCD163 levels were significantly higher among COVID-19 patients, independently of ICU admission requirement, compared to the control group. We found a significant correlation between sCD14 levels and other inflammatory markers, particularly Interleukin-6, in the non-ICU patients’ group. sCD163 showed a moderate positive correlation with the time at sampling from admission, increasing its value over time, independently of severity group. Conclusions. Monocyte-macrophage activation markers are increased and correlate with other inflammatory markers in SARS-Cov-2 infection, in association to hospital admission. These data suggest a potentially preponderant role for monocyte-macrophage activation in the development of immunopathology of covid19 patients.